Korelasi Kadar Prokalsitonin dengan Angka Leukosit pada Pasien Sepsis Bakterial di Ruang Rawat Intensif RSUP Dr. Sardjito Yogyakarta - Utami, Vengky; Wisudarti, Calcarina Fitriani Retno; Jufan, Akhmad Yun (Jurnal Komplikasi Anestesi, 2021)
Background: The Surviving Sepsis Campaign recommends using procalcitonin to help diagnose acute systemic infections, infection resolution, escalation, and discontinue antibiotic therapy on sepsis patients. Unfortunately, procalcitonin testing is very expensive and not yet available in all hospitals. Alternative biological markers are needed besides procalcitonin. The component of differentiated leukocyte count is known to be correlated with procalcitonin. Methods: This is a cross-sectional retrospective study and includes all bacterial sepsis patients that have been treated in the Dr. Sardjito General Hospital ICU between 1 January - 31 December 2019. Data of 436 laboratory examinations have been collected from 104 patients’ medical records, then processed with SPSS version 26 to look for correlations between procalcitonin with each component of leukocyte count value, followed by regression analysis between procalcitonin and leukocyte count values. Results: We found very strong positive correlation (R2 = 0.823, p <0.05) in multivariate analysis between procalcitonin levels and differential leucocyte count. There was moderate positive correlation in bivariate correlation between procalcitonin and leucocytes (r = 0.279, p <0.05) and absolute monocytes (r = 0.254, p> 0.05). There was also very weak positive correlation between procalcitonin and absolute neutrophils (r = 0.239, p <0.05), percentage neutrophils (r = 0.078, p <0.05), absolute eosinophils (r = 0.148, p<0.05), percentage eosinophils (r = 0.104, p<0.05), absolute basophils (r = 0.029, p>0.05), percentage basophils (r = 0.011, p> 0.05), absolute lymphocytes (r = 0.121, p>0.05), lymphocyte percentage (r = 0.074, p> 0.05), monocyte percentage (r = 0.208, p>0.05), absolute immature granulocytes (r = 0.064, p <0.05) , and percentage immature granulocytes (r = 0.029, p> 0.05). Conclusion: There was a strong positive correlation between procalcitonin levels and leukocyte count in bacterial sepsis patients treated in Dr. Sardjito General Hospital, Yogyakarta intensive care unit